In Situ Recrystallization of Polyoxometalates: From 0D Architectures to 2D Inorganic–Organic Hybrids. Issue 10 (26th February 2013) - Liu, Xuan; An, Haiyan; Chen, Zhaofei; Zhang, Hua; Hu, Ying; Zhu, Guibo; Geletii, Yurii V.; Hill, Craig L.
Abstract: The compound (4‐H2 pya)3 [Al(OH)6 Mo6 O18 ]· 5H2 O (1 ) transforms into two 2D hybrid species (4‐Hpya)[(4‐Hpya)Ln(H2 O)5 ]2 [Al(OH)6 Mo6 O18 ]2 · 13H2 O Ln = Ce (2 ), La (3 ); 4‐Hpya = 3‐(4‐pyridyl)acrylic acid in the mother liquor through crystal dissolution and recrystallization; this represents a rare example of in situ recrystallization involving polyoxometalate crystal systems. All compounds were characterized by elemental analysis, IR and UV/Vis spectroscopy, thermogravimetric analysis, powder X‐ray diffraction, and single‐crystal X‐ray diffraction. Compound1 is a 0D architecture consisting of protonated 4‐H2 pya ligands and [Al(OH)6 Mo6 O18 ] 3– polyoxoanions, which are connected through hydrogen‐bonding and electrostatic interactions. Isostructural compounds2 and3 crystallize in the triclinic crystal system, space group P 1, and exhibit a unique 2D framework composed of [Al(OH)6 Mo6 O18 ] 3– polyoxoanions and Ln‐4‐Hpya coordination complexes with a rare (3, 4)‐connected net. The magnetic properties of compound2 were studied by measuring its magnetic susceptibility in the temperature range 2.0–300.0 K. Abstract : 0D hybrid compound1 transforms into 2D hybrid architecture2 in the mother liquor during recrystallization through crystal disassembly and reassembly.